Morphological and molecular characterization of a novel myxosporean parasite Myxobolus bejeranoi n. sp. (Cnidaria: Myxosporea) from hybrid tilapia in Israel - Lövy, Alena; Smirnov, Margarita; Brekhman, Vera; Ofek, Tamir; Lotan, Tamar (Parasitology research, 2018)
Myxosporean infections can cause severe damage to commercially grown tilapia. Here, we report a novel myxosporean that was found in gills of Oreochromis aureus male × Oreochromis niloticus female, which is an important aquaculture tilapia hybrid in Israel. Three-month-old fish were found to have cysts located in gill muscle tissue, which were filled with both immature and mature spores. Affected fish displayed higher mortality rate. Spore dimensions (10.8 ± 0.7 μm length × 6.8 ± 0.6 μm width) and molecular characterization using 18S ribosomal DNA revealed that the unknown parasite belongs in the Myxobolus clade. Based on the infection site, spore morphology and molecular characterization, we describe this parasite as Myxobolus bejeranoi n. sp. (MF401455). Phylogenetic analysis showed that the new species is most closely related to two Myxobolus spp. from O. niloticus in Egypt and Ghana.
Keywords: parazitární nemoci u zvířat; Gills; žábry; mužské pohlaví; Myxobolus; Israel aquaculture; DNA, Ribosomal; Muscles; Spores; RNA ribozomální 18S; spory; Izrael; ženské pohlaví; zvířata; nemoci ryb; fylogeneze; svaly; ribozomální DNA; RNA, Ribosomal, 18S; Israel; Tilapia; Parasitic Diseases, Animal; Pathogenic parasite; Fish Diseases; Myxosporea; Female; Phylogeny; Oreochromis hybrid; Male; Animals